Endovascular and Surgical Treatment of Unruptured MCA Aneurysms: Meta-Analysis and Review of the Literature - Spiros L. Blackburn; Abdelrahman M. Abdelazim; Andrew B. Cutler; Kevin T. Brookins; Kyle M. Fargen; Brian L. Hoh; Yasha Kadkhodayan (Stroke Research and Treatment)
Introduction. The best treatment for unruptured middle cerebral artery (MCA) aneurysms is unclear. We perform a meta-analysis of recent publications to evaluate the results of unruptured MCA aneurysms treated with surgical clipping and endovascular coiling. Methods. A PubMed search for articles published between January 2004 and November 2013 was performed. The R statistical software package was used to create a random effects model for each desired incidence rate. Cochran’s Q test was used to evaluate possible heterogeneity among the rates observed in each study. Results. A total of 1891 unruptured MCA aneurysms, 1052 clipped and 839 coiled, were included for analysis. The complete occlusion rate at 6–9 months mean follow-up was 95.5% in the clipped group and 67.8% in the coiled group (P<0.05). The periprocedural thromboembolism rate in the clipping group was 1.8% compared with 10.7% in the aneurysms treated by coiling (P<0.05). The recanalization rate was 0% for clipping and 14.3% for coiling (P=0.05). Modified Rankin scores of 0–2 were obtained in 98.9% of clipped patients compared to 95.5% of coiled (NS). Conclusions. This review weakly supports clipping as the preferred treatment of unruptured MCA aneurysms. Clinical outcomes did not differ significantly between the two groups.